SYSTEMANIZE METHODS OF STUDYING THE "HUMAN-CLOTHING" SYSTEM IN DYNAMICS AND ANALYZE THEIR EQUIPMENT. - Nematova L.H; Qodirova D.X (Western European Studies, 2024)
Methods of measuring time are the application of any regular reproducible process. In this case, the amount of this process between two events is simply calculated. The more precisely the steps are calculated, the more accurately they describe the time spacing between two consecutive events. There is a time ethanol available for each step of the process.
Keywords: Clothing design; asymmetry; symmetry; architecture; formation; harmonization